Risk Factors For Hand Dermatitis In Hospital Nurses In Sukoharjo - Budi Rahmawati; Ratih Pramuningtyas (Eduvest - Journal of Universal Studies, 2021)
Hands are organs that play a role in communication, because in some jobs shaking hands is crucial. People who are at risk of getting this disease include health workers and it will have an impact in the future. The purpose of this study was to determine the risk factors for hand dermatitis in hospital nurses in Sukoharjo. This type of research is descriptive analytic research with cross sectional design. Cross sectional is a non-experimental research to study the dynamics of the correlation between risk factors and effects, by approach, observation or data collection all at once (point time approach). The research was conducted at dr. New Oen Solo. The research was conducted in November-February 2020. Based on the analysis and discussion, it can be concluded that risk factors, wet work, atopic history, age, gender, years of service are not related to the incidence of hand dermatitis in hospital nurses in Sukoharjo.